The Influence Of Leadership Style And Work Culture On Employee Performance At PT. Citra Putera Utama Pringsewu - Lambang Murvit Aziz; Iskandar Ali Alam (Cita konsultindo, 2024)
This study aims to determine the effect of leadership style and work culture on employee performance at PT. The image of the main son of Pringsewu. The population of this study were employees at PT. The image of the main son of Pringsewu. The sampling method used was the saturated sampling method or census sampling, so that the sample used was 57 respondents. Data collection was carried out through a survey with a previously designed questionnaire. After the data was collected, the analysis was carried out using SPSS software, including multiple linear analysis, t-test for partial hypothesis testing, F-test for ANOVA hypothesis testing, and closing with a determination coefficient test to assess the strength of the relationship between variables. The results of this study indicate that leadership style and work culture, both partially and together, have an effect on Employee Performance at PT. The image of the main son of Pringsewu. For other researchers who intend to conduct repeat research or research similar to this study, it is hoped that improvements can be made. Improvements can be made by using more complete data analysis or by adding several variables that can theoretically and empirically affect employee performance. So that it is expected to obtain better and more comprehensive research results than the results of this study.